Organisierendes Arbeiten: Zur Performativität von Projekten - Kalff, Yannick (transcript, 2018)
What do people do when they work in projects? This book shows that projects stand for independent and creative yet also for strictly controlled work. That contradiction is resolved in work that organizes.